Economic Adjustment : Policies and Problems; Papers Presented at a Seminar held in Wellington, New Zealand, February 17-19, 1986 - Holmes, Frank (International Monetary Fund, 1987)
This volume, edited by Sir Frank Holmes of the Institute of Policy Studies in New Zealand, contains the proceedings of a seminar held in Wellington, New Zealand. The seminar concentrates on problems of economic adjustment facing countries in the South Pacific. Subjects covered in the eight papers include case studies of adjustment in developed and edveloping countries, and the role of private capital aid and exchange rate, pricing, and trade policies in adjustment and development.